HIV Testing and Preventive Services Accessibility Among Men Who Have Sex With Men at High Risk of HIV Infection in Beijing, China. Issue 6 (February 2015) - Zhao, Yuejuan; Zhang, Li; Zhang, Heng; Xia, Dongyan; Pan, Stephen W.; Yue, Hai; Lu, Hongyan; Xing, Hui; He, Xiong; Shao, Yiming; Ruan, Yuhua
Abstract : Abstract: The HIV epidemic among men who have sex with men (MSM) has been increasing at an alarming rate in most areas of China in recent years. Many Chinese MSM still lack sufficient access to HIV prevention services, despite ongoing scale-up of comprehensive HIV testing and intervention services. The purpose of this study was to investigate utilization of HIV testing and prevention services, and related factors that influence the MSM people to access HIV test or other services to prevent HIV among MSM in Beijing, China. Three successive cross-sectional surveys of MSM were conducted in Beijing from September 2009 to January 2010, September 2010 to January 2011, and September 2011 to January 2012. Demographic and behavioral data were collected and analyzed. Blood samples were tested for HIV and syphilis. Three models were established to analyze factors associated with HIV testing and preventive services. Of the 1312 participants, prevalence of HIV and syphilis was 7.9% and 15.4%, respectively. Sixty-nine percent ever had an HIV test, 56.2%, 78.7%, and 46.1% received HIV test, free condom/lubricants, and sexually transmitted infection services in the past 12 months (P12M), respectively. MSM with larger social networks and who knew someone infected with HIV were more likely to receive HIV testing and preventive services; lower degrees of stigma and discriminatory attitudes toward HIV/AIDS were positively associated with having an HIV test, whereas unprotected anal intercourse in the past 6 months (P6M) was associated with less preventive services participation. The most reported barriers to HIV testing were fear of testing HIV positive (79.3%) and perceiving no risk for HIV (75.4%). Almost all participants felt that ensuring confidentiality would encourage more MSM to have an HIV test. The two main reasons for not seeking HIV test was not knowing where to go for a test (63.2%) and perceiving low risk of HIV infection (55.1%). Given a high prevalence of HIV, syphilis, and risky behaviors and a relatively low HIV testing rate among MSM in Beijing, more efforts are urgently needed to address barriers to HIV testing and improve accessibility of prevention services.